Den enkla naturen och andligheten - Gaunitz, Anne (2006)
This paper treats the physical environments influence on the spritual experience that comes with pilgrimage. The paper deals with a case study on a two-day pilgrimage in Sweden. The method triangulating has been used in the forms; participating observation, interviews and one poll. The question at issue has also included what spiritualism really is för the persons in the paper. The interviews are also concerned with the general environmental significance on pilgrimages.